2012
DOI: 10.1128/aac.01505-12
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synergy between Clofazimine and Amikacin in Treatment of Nontuberculous Mycobacterial Disease

Abstract: Disease caused by nontuberculous mycobacteria (NTM) is increasing in frequency. The outcome of treatment for NTM lung disease is poor, particularly lung disease caused by Mycobacterium simiae and M. abscessus. Exploring synergy between active available drugs is a sensible way forward given the lack of new active drugs. We tested for synergy between amikacin and clofazimine, using standardized methods, in 564 consecutive clinical isolates identified as 21 species of rapidly growing mycobacteria, 16 clinical M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
101
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 23 publications
4
101
1
1
Order By: Relevance
“…Clofazimine is the prototype riminophenazine antibiotic with in vitro activity against most mycobacteria (1,4). Its main clinical use so far is in the multidrug treatment of leprosy and multidrugresistant tuberculosis (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clofazimine is the prototype riminophenazine antibiotic with in vitro activity against most mycobacteria (1,4). Its main clinical use so far is in the multidrug treatment of leprosy and multidrugresistant tuberculosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed in vitro synergy between clofazimine and amikacin against both rapidly and slowly growing NTM (1,6). The combination clarithromycin-clofazimine also showed synergy against MAC strains in checkerboard evaluation (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest two possible explanations: first, the initiation of HAART treatment in the HIV cases improves the immunological status of the patient; and second, the combination of antibiotics could act synergistically improving antimycobacterial drug activity. Indeed, two studies showed in vitro synergy in non-tuberculous mycobacteria, which included M. simiae and related species 11,12 ; an alternative to the classic AST could be the synergy study of the drugs used.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be needed to differentiate treatment failure from reinfection and to identify better therapeutic regimens with the addition of potentially effective drugs, such as intravenous or inhaled amikacin, inhaled liposomal amikacin, fluoroquinolones, and clofazimine, in these patients with NB MAC-LD (26)(27)(28)(29).…”
mentioning
confidence: 99%